2010
DOI: 10.1088/0957-4484/21/23/235602
|View full text |Cite
|
Sign up to set email alerts
|

Local and CMOS-compatible synthesis of CuO nanowires on a suspended microheater on a silicon substrate

Abstract: This paper presents the synthesis of CuO nanowires using a localized thermal heating method in ambient air. It employs local heat sources defined in micro-resistive heaters fabricated by a standard polysilicon-based surface micromachining process instead of a global furnace heating. Since the synthesis is performed globally at room temperature, the presented process is compatible with standard CMOS. The synthesized CuO nanowires are characterized by scanning electron microscopy, transmission electron microscop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 25 publications
(34 reference statements)
0
36
0
Order By: Relevance
“…Cupric oxide, CuO, which is a p-type semiconductor [1] (indirect bandgap of 1.2 to 1.5 eV) has been widely exploited for devices applications, such as an active electrode material for Li-ion batteries, field emission [FE]emitters, heterogeneous catalysts, gas sensors, hetrostructure and solar cells [2][3][4][5][6][7]. Several methods have been developed to prepare CuO nanostructures, such as chemical vapor deposition (CVD) [8], laser vaporization [9], electrochemical techniques [10], hydrothermal treatment [11] inexpensive wet chemical method [12], thermal oxidation methods [13] and the Sol-Gel method [14].…”
Section: Introductionmentioning
confidence: 99%
“…Cupric oxide, CuO, which is a p-type semiconductor [1] (indirect bandgap of 1.2 to 1.5 eV) has been widely exploited for devices applications, such as an active electrode material for Li-ion batteries, field emission [FE]emitters, heterogeneous catalysts, gas sensors, hetrostructure and solar cells [2][3][4][5][6][7]. Several methods have been developed to prepare CuO nanostructures, such as chemical vapor deposition (CVD) [8], laser vaporization [9], electrochemical techniques [10], hydrothermal treatment [11] inexpensive wet chemical method [12], thermal oxidation methods [13] and the Sol-Gel method [14].…”
Section: Introductionmentioning
confidence: 99%
“…19 However, there are few studies in the literature to integrate Al/CuO nEMFs with SCB in order to realize energetic initiators, although this is very interesting for the practical applications of Al/CuO nEMFs. [20][21][22] In this paper, energetic initiators realized by integrating Al/CuO nEMFs with SCB (SCB-Al/CuO) were fabricated and characterized for nanothermite combustion performance. An understanding of the stages of rapid combustion was gained, and critical design parameters were determined.…”
Section: Introductionmentioning
confidence: 99%
“…[79][80][81][82][83][84][85][86] We have also demonstrated that an array of metallic microbridges such as molybdenum on ordinary glass substrates can be selectively heated up to 1200 °C while maintaining the substrate temperature below 100 °C (Figure 7 b), and have used the bridges for the synthesis of various materials, including polycrystalline silicon (p-Si) [ 87 ] and SWCNTs, [ 88 ] as well as for the annealing of lanthanum hexaboride (LaB 6 ) [ 89 ] and EL patterning. [ 90 ] We also successfully synthesized ZnO nanorods and ZnO/GaN coreshell nanorod heterostructures (Figure 7 c).…”
Section: Progress Reportmentioning
confidence: 99%